Non-surgical treatments after face trauma sequelae: A literature review (Research, Society and Development, 2023)
Trauma is defined as a set of functional and anatomical changes resulting from localized and/or generalized impacts. Aesthetic sequelae caused by traumatic events can be treated post-operatively through multidisciplinary teams, which aim to restore affected functions and improve the patient's quality of life. Non-surgical treatments, such as physiotherapy, laser therapy, botulinum toxin and hyaluronic acid, contribute to the evolution of treatment, reducing post-surgical complications and sequelae, making the post-trauma prognosis superior and more predictable. Therefore, the objective of this work is to demonstrate, through a literature review, non-surgical treatments through the importance of these interventions in post-trauma motor and psychological functions as well as the protocols established in the literature. In the studies analyzed, they showed beneficial effects on healing, reduction of edema, pain, and also on facial deformities resulting from sequelae.